2014
DOI: 10.1093/carcin/bgu107
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cancer pleiotropic analysis of endometrial cancer: PAGE and E2C2 consortia

Abstract: Genome-wide association studies (GWAS) have identified a large number of cancer-associated single nucleotide polymorphisms (SNPs), several of which have been associated with multiple cancer sites suggesting pleiotropic effects and shared biological mechanisms across some cancers. We hypothesized that SNPs associated with other cancers may be additionally associated with endometrial cancer. We examined 213 SNPs previously associated with 14 other cancers for their associations with endometrial cancer in 3758 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…911 Germline TET2 variants are associated with an increased risk of prostate 12,13 and endometrial 7 cancers, and melanoma. 8 Thus, germline and somatic alterations implicate TET2 as a cancer gene in MPDs and epithelial cancers.…”
Section: Introductionmentioning
confidence: 99%
“…911 Germline TET2 variants are associated with an increased risk of prostate 12,13 and endometrial 7 cancers, and melanoma. 8 Thus, germline and somatic alterations implicate TET2 as a cancer gene in MPDs and epithelial cancers.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate pleiotropic associations of cancer GWAS loci on risks of EA and BE. Although our study sample size is moderate, the combined number of EA and BE cases is larger than that of most previous studies on cancer pleiotropy (4, 7-9). For SNPs with MAF of 0.3 (the average MAF of all tested SNPs), we had 80% statistical power to detect an OR of 1.21 per minor allele for analyses on EA/BE combined, with a Bonferroni-corrected type I error rate of 5%.…”
Section: Discussionmentioning
confidence: 88%
“…Studies investigating pleiotropic effects of GWAS-identified risk variants have revealed additional risk loci for endometrial, colorectal, and pancreatic cancer, but not for estrogen-receptor (ER)-negative breast cancer (ER-positive cancers were not investigated), prostate cancer, or non-Hodgkin lymphoma (4, 7-9). Some studies, including those of non-Hodgkin lymphoma, endometrial cancer, and colorectal cancer, investigated cancer GWAS hits while studies of pancreatic cancer, prostate cancer, and ER-negative breast cancer investigated cancer and non-cancer GWAS-hits (4, 7-9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genome-wide pleiotropy scan approach has previously yielded novel associations for risk of pancreatic adenocarcinoma [11] and endometrial [12] and colorectal cancer [13]. The hypothesized pleiotropic effects (when a genetic locus is associated with multiple phenotypes or phenotypic traits) [14] are especially meaningful in cancer.…”
Section: Introductionmentioning
confidence: 99%